Photographic Parameters of Reprography - Rajagopal, C. (Journal of Information and Knowledge, 1980)
The modern reprographic processes rely heavily on photographic techniques and hence the important photographic parameters of reprography are briefly outlined in this paper. Special emphasis is placed on optical parameters, photographic equipment and correct processing.